2009
DOI: 10.1038/nri2471
|View full text |Cite
|
Sign up to set email alerts
|

The ageing immune system: is it ever too old to become young again?

Abstract: Ageing is accompanied by a decline in the function of the immune system, which increases susceptibility to infections and can decrease the quality of life. The ability to rejuvenate the ageing immune system would therefore be beneficial for elderly individuals and would decrease health-care costs for society. But is the immune system ever too old to become young again? We review here the promise of various approaches to rejuvenate the function of the immune system in the rapidly growing ageing population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
300
2
8

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 378 publications
(316 citation statements)
references
References 58 publications
6
300
2
8
Order By: Relevance
“…At this point, it is worthwhile noting that in humans, as well as in mice, B-cell production in the bone marrow decreases with age and correlates with an increased incidence of auto-antibodies in the serum [5,[38][39][40][41]. In order to test the hypothesis that decreased B-cell production in the bone marrow increases the chance of developing auto-immunity, other mutant mice in which bone marrow B-cell development is reduced should be analyzed.…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…At this point, it is worthwhile noting that in humans, as well as in mice, B-cell production in the bone marrow decreases with age and correlates with an increased incidence of auto-antibodies in the serum [5,[38][39][40][41]. In order to test the hypothesis that decreased B-cell production in the bone marrow increases the chance of developing auto-immunity, other mutant mice in which bone marrow B-cell development is reduced should be analyzed.…”
Section: Tolerance Checkpoints In B-cell Development Large Pre-bii Cellsmentioning
confidence: 99%
“…Thus competition for newly formed B cells to enter the peripheral B-cell pool is far less in surrogate light chain deficient mice than in WT mice. Therefore, it could be envisaged that negative selection of immature auto-reactive B cells in the bone marrow of these mice is less stringent, resulting in higher titers of auto-antibodies.At this point, it is worthwhile noting that in humans, as well as in mice, B-cell production in the bone marrow decreases with age and correlates with an increased incidence of auto-antibodies in the serum [5,[38][39][40][41]. In order to test the hypothesis that decreased B-cell production in the bone marrow increases the chance of developing auto-immunity, other mutant mice in which bone marrow B-cell development is reduced should be analyzed.…”
mentioning
confidence: 99%
“…Responses to vaccination are also less effective in the elderly. These manifestations are thought to reflect an age‐related functional decline in the immune system (Dorshkind et al ., 2009). An integrated understanding of the aging immune system is therefore essential for the delivery of optimal healthcare to the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…9 Aging of the immune system, referred to as immunosenescence, is characterized by a decrease in cell-mediated immune function and a reduction of humoral immune responses. 10,11 Clinically, immunosenescence is partially responsible for increased prevalence and severity of infectious diseases as well as low efficacy of vaccinations in elderly patients. 10 Age-related decreases in immunosurveillance against cancer has also been suggested as a contributing factor to increased cancer rates, such as lung cancer, in elderly patients.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Clinically, immunosenescence is partially responsible for increased prevalence and severity of infectious diseases as well as low efficacy of vaccinations in elderly patients. 10 Age-related decreases in immunosurveillance against cancer has also been suggested as a contributing factor to increased cancer rates, such as lung cancer, in elderly patients. 12 Furthermore, preclinical studies in animal models have indicated that antitumor immunotherapeutic interventions are less effective in aged animals.…”
Section: Introductionmentioning
confidence: 99%